IMPLEMENTASI KEBIJAKAN PROGRAM LAYANAN RAKYAT UNTUK SERTIPIKASI TANAH (LARASITA) DI KANTOR PERTANAHAN KABUPATEN DONGGALA - Nurdin, Nurdin (Katalogis, 2017)
This Research Target is to know and analyse the Policy Implementation Program the Larasita program at Office of Land  Regency Donggala.  Why policy implementation the Service of People  Sertipikasi Lan in office of Land of Regency Donggala not walk better. This Research Type is research qualitative with the informant selected by  six of people. Data collecting use the perception technique, interview and documentation. Technique analyse the data used  that is ( 1) Data collecting (2) Reduce the Data (3) Data Presentation (4) Verification ( 5)  Conclusion. Theory used  is theory of Van of metre and Horn Van in (Subarsono, 2005), measuring policy implementation: (1) standard And Target (2) Resource (3) Communications (4) Characteristics Executor (5) Social Condition, economics and political (6) Disposition. Pursuant to result of research and analysis conducted researcher [concluded that policy implementation Program the Larasita not yet walked better, what is elaborated as follows: (1) policy Implementation Program Larasita in Office of Land;Ground of Regency Donggala seen from factor of standard and policy target not yet walked better (2) policy Implementation Program Larasita in Office of Land of Regency Donggala seen from Resource factor not yet walked better this matter is seen from medium and prasarana not yet adequate and also sum up the officer which still office of Regency Landd Less Donggala. (3)Policy implementation Program Larasita in Office of Land of Regency Donggala seen from communication factor characteristic, political and economic social condition and also disposition factor not yet walked better, this matter is seen from facility which disedikan not yet adequate and also supportedresult of interview with the informan done/conducted  in research location.